Strategic Roles of Teachers in Promoting Interfaith Education for Unity in Central Kalimantan, Indonesia - Hamu, Fransiskus Janu; Pudjiarti, Emiliana Sri; Jimmy, Andreas; Chang, William (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to explore the strategic role of teachers in building character education through a multireligious approach in Central Kalimantan. Using a mixed-method approach with a sequential explanatory design, the study combined quantitative analysis of the structural relationships between spiritual engagement, pro-social engagement, interfaith cooperation, and social integration with thematic analysis of in-depth interviews with teachers from five religious traditions (Muslim, Catholicism, Protestantism, Buddhism, and Hinduism). Quantitative data analysis used structural equation modelling with a partial least squares approach and qualitative data used thematic analysis with NVivo 14 software. The results revealed that spiritual engagement has a significant effect on interfaith cooperation and an indirect effect on social integration. In contrast, pro-social engagement has a significant effect on both interreligious cooperation and social integration. Thematic findings showed the convergence of teachers' practices in integrating universal spiritual values, facilitating interfaith pro-social activities, developing interfaith dialogue, and creating an inclusive learning environment that supports students' character-building. Expert validation confirmed the successful implementation of interpretive and integrative approaches in transforming religious education from an exclusive to an inclusive, transformative model.